Performance of Grid-connected Photovoltaic System in Equatorial Rainforest Fully Humid Climate of Malaysia - Mohamad Zhafran Hussin; A. M. Omar; Z. M. Zain; S. Shaari (Institute of Advanced Engineering and Science, 2013)
This paper presents a result obtained from a comparative study among three different photovoltaic (PV) module technologies for grid-connected photovoltaic system (GCPV) under Malaysia’s real operating conditions. The obtained results were slightly different from the performance ratio (PR) investigation which showed the average annual performance of 78.2% for polycrystalline, 94.6% for a-Si thin-film and 81% for monocrystalline PV technologies over four years monitored period. The outdoor evaluation results showed that a-Si thin-film PV modules demonstrate the highest and better in terms of final yield, performance ratio and PV array/system efficiency over the entire monitored period. In other hands, a-Si thin-film demonstrated the reliability and better in system performance